Immunology of Cryptococcal Infections: Developing a Rational Approach to Patient Therapy - Elsegeiny, Waleed; Marr, Kieren A.; Williamson, Peter R. (Frontiers in Immunology, 2018)
Cryptococcal meningoencephalitis is responsible for upwards of 15% of HIV-related deaths worldwide and is currently the most common cause of non-viral meningitis in the US, affecting both previously healthy and people with immune suppression caused by cancer chemotherapy, transplantation, and biologic therapies. Despite a continued 30–50% attributable mortality, recommended therapeutic strategies have remained largely unchanged since the 1950s. Recent murine models and human studies examining the role of the immune system in both susceptibility to the infection as well as host damage have begun to influence patient care decisions. The Damage Framework Response, originally proposed in 1999, was recently used to discuss dichotomous etiologies of host damage in cryptococcal disease. These include patients suffering microbiological damage with low host immunity (especially those immunosuppressed with HIV) and those having low (live) microbiological burden but high immune-mediated damage (HIV-related immune reconstitution syndrome and non-HIV-related postinfectious inflammatory response syndrome). Cryptococcal disease in previously healthy hosts, albeit rare, has been known for a long time. Immunophenotyping and dendritic cell-T cell signaling studies on cerebral spinal fluid of these rare patients reveal immune capacity for recognition and T-cell activation pathways including increased levels of HLA-DR and CD56. However, despite effective T-cell signals, brain biopsy and autopsy specimens demonstrated an M2 alternative macrophage polarization and poor phagocytosis of fungal cells. These studies expand the paradigm for cryptococcal disease susceptibility to include a prominent role for immune-mediated damage and suggest a need for careful individual consideration of immune activation during therapy of cryptococcal disease in diverse hosts.